2016
DOI: 10.1111/resp.12793
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of obstructive lung disease in a suburban population of Malaysia: A BOLD collaborative study

Abstract: Background and objective: As a Burden of Obstructive Lung Disease (BOLD) collaboration, we studied the prevalence of chronic obstructive pulmonary disease (COPD) and its associated risk factors in a suburban population in Malaysia. Methods: Nonhospitalized men or women of age ≥ 40 years from a Penang district were recruited by stratified simple random sampling. Participants completed detailed questionnaires on respiratory symptoms and exposure to COPD risk factors. Prebronchodilator and post-bronchodilator spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…The high degree of breathlessness, poor health-related quality of life and frequent exacerbations in our cohort may represent a more severe COPD disease that were not adequately addressed or treated in many of our patients. Such frequent exacerbation rates were also reported in other studies involving Malaysia [4,5]. The small number of first-time exacerbators indicates that hospitalized setting is not the ideal place to diagnose COPD early.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The high degree of breathlessness, poor health-related quality of life and frequent exacerbations in our cohort may represent a more severe COPD disease that were not adequately addressed or treated in many of our patients. Such frequent exacerbation rates were also reported in other studies involving Malaysia [4,5]. The small number of first-time exacerbators indicates that hospitalized setting is not the ideal place to diagnose COPD early.…”
Section: Discussionmentioning
confidence: 51%
“…In collaboration with Burden of Obstructive Lung Disease (BOLD) initiative, we have recently estimated the COPD prevalence at 3.4% in a suburban population of Malaysia [4]. In a population-based survey of Asia-Pacific countries [5], over half of the interviewed COPD patients from Malaysia reported ≥one exacerbation in the past twelve months and many experienced negative impact on work and activities.…”
Section: Introductionmentioning
confidence: 99%
“…In collaboration with international Burden of Obstructive Lung Disease (BOLD), we published the first robust population-based COPD epidemiology data for Malaysia in 2016. 2 We showed that the estimated prevalence of airflow obstruction (principal COPD feature) of a local suburban area was low (3.4% and 6.5% based on NHANES-derived LLN criteria and fixed forced expiratory volume in 1 s/vital capacity (FEV 1 /VC) ratio, respectively) compared with most sites globally including Asian cities such as Guangzhou, Mumbai and Manila. This appeared to be so despite a similarly high Figure 1 The indelible ink on finger as proof of voting in the 2018 Malaysian general election.…”
mentioning
confidence: 89%
“…For instance, Loh et al, in a population-based spirometric testing study in Malaysia reported a lower prevalence of COPD than expected. 4 Nevertheless, the long-term impact of an uncontrolled cigarette industry on an ageing population in Asian countries with large populations is a very grave concern.…”
Section: Epidemiology and Diagnosismentioning
confidence: 99%